2004
DOI: 10.1007/s00268-004-7561-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Thyroid Cancer in Adult Patients Exposed to Ionizing Radiation due to the Chernobyl Nuclear Accident: 5‐Year Comparative Investigations Based on the Results of Surgical Treatment

Abstract: The aim of study was to compare clinical and pathologic findings of surgically removed thyroid tumors in adults with or without history of irradiation due to the Chernobyl accident. From 1990 to 2003, 2363 adults with no evidence of radiation influence in their history (group A) have undergone operation for thyroid nodules. During the same period, 311 patients (born before 1969) with strict evidence of Chernobyl irradiation also underwent operation (group B). Both groups were similar in age, sex, and preoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
9

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 11 publications
(7 reference statements)
0
15
1
9
Order By: Relevance
“…These include thyroid cancer in children [4,[20][21][22] and modifications of the cardiovascular system [7,14,23,24] and actual cardiovascular disorders, both in children [14,25] and in liquidators [26]. Only one experimental study has examined the cardiovascular effects of chronic contamination of animals by 137 Cs doses comparable to the post-accident exposure of the local population [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include thyroid cancer in children [4,[20][21][22] and modifications of the cardiovascular system [7,14,23,24] and actual cardiovascular disorders, both in children [14,25] and in liquidators [26]. Only one experimental study has examined the cardiovascular effects of chronic contamination of animals by 137 Cs doses comparable to the post-accident exposure of the local population [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the youngest children in the contaminated areas are developing thyroid cancer [4], bone disorders [5], and nervous and digestive system disorders [6,7]. As a few animal experiments have assessed the biological effects of chronic exposure to 137 Cs, we studied the results of 137 Cs contamination of rats on various physiological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 235 studies were retrieved for further investigation, and 41 studies (14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54) met the final selection criteria and were included in the analysis. All 41 studies were observational studies published in peer-reviewed journals between 1989 and 2012.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…It has been reported previously that thyroid cancer in liquidators was significantly more aggressive than in adults with no history of irradiation (Cherenko et al 2004). However little is known about the pathological and molecular characteristics of Chernobyl liquidators' thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…All patients in the liquidator group in this study were Ukrainians and presented an official certificate of recovery work. However, no information could be obtained concerning their individual irradiation status (Cherenko et al 2004). All subjects in NI Ukranian patient group lived outside the 'officially contaminated' areas and there is no evidence that they were exposed to contamination from Chernobyl.…”
Section: Thyroid Tissuementioning
confidence: 99%